The evaluation of an online mindfulness program for people with multiple sclerosis: study protocol - Sesel, Amy-Lee (BMC Neurol, 2019)
BACKGROUND: Multiple sclerosis (MS) is a neurological disease of the central nervous system and is associated with many psychosocial symptoms that are difficult to manage including low mood, anxiety, fatigue and pain, as well as low health-related quality of life. Internet-based psychosocial interventions that use mindfulness-based approaches are gathering much attention in recent literature, particularly in the treatment of chronic illnesses. However, no large randomized controlled trials have been done examining the efficacy of such interventions for people with MS (PwMS). METHODS/DESIGN: This study is a randomised controlled trial of an online mindfulness-based intervention (MBI) for PwMS. Participants will be randomised to receive either the MBI or offered the intervention after a waiting period. All participants will be assessed to determine whether they have a history of recurrent depressive disorder. The primary outcome will be severity of depression, according to the Centre of Epidemiology Depression Scale. Secondary outcomes will be anxiety severity, fatigue, pain and quality of life. Assessments will be conducted pre, post-treatment, at three and six-month follow-up. The online mindfulness-based program was developed in collaboration with end-users (n = 19 PwMS) who gave feedback about what would be feasible and acceptable, and the draft program was reviewed by both experts and patients. DISCUSSION: Multiple sclerosis is the most common acquired chronic neurological disease amongst young adults and is associated with a range of symptoms that can be difficult to cope with. In face-to-face interventions, a MBI demonstrated the largest effect in a recent meta-analysis of psychological treatments for PwMS, but MBIs for PwMS have not been delivered online. Hence, this trial will confirm whether MBIs can be efficacious when delivered online. A range of symptoms are assessed as outcomes so that the nature of benefits associated with the online MBI can be ascertained. TRIAL REGISTRATION: ACTRN12618001260213. Date of Registration: 25/07/2018. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12883-019-1356-9) contains supplementary material, which is available to authorized users.